IMPLEMENTATION OF KOKURIKULER LEARNING IN THE INDEPENDENT CURRICULUM AT THE DRIVING SCHOOL OF SMA NEGERI 2 BATU CITY - Rofiq, Ahmad Ainur; Z, Riza Arif M; Ikhwan, Ari Afiful; Ali, M. Makhrus (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
Kokurikuler learning is a learning activity in the independent curriculum, this learning is carried out with an interdisciplinary learning strategy, namely by combining several knowledge groups in a learning project. The aim of this kokurikuler learning activity is to develop the potential of students, therefore this learning activity is carried out through the Strengthening Pancasila Student Profile Project activity. This research was carried out at SMA Negeri 2 Batu City driving school using a qualitative approach, this type of research is a case study. This research aims to understand the procedures for implementing co-curricular learning at SMA Negeri 2 Batu City which includes aspects of planning, implementation and evaluation of co-curricular learning. The results of this research are 6 stages in learning planning and are carried out with interdisciplinary learning, assessment and formative assessments are carried out to see the extent of students' development, this assessment is carried out with the facilitation team having provided a rubric called the observation rubric.